2021
DOI: 10.3390/cancers13061244
|View full text |Cite
|
Sign up to set email alerts
|

3D Pharmacophore-Based Discovery of Novel KV10.1 Inhibitors with Antiproliferative Activity

Abstract: (1) Background: The voltage-gated potassium channel KV10.1 (Eag1) is considered a near- universal tumour marker and represents a promising new target for the discovery of novel anticancer drugs. (2) Methods: We utilized the ligand-based drug discovery methodology using 3D pharmacophore modelling and medicinal chemistry approaches to prepare a novel structural class of KV10.1 inhibitors. Whole-cell patch clamp experiments were used to investigate potency, selectivity, kinetics and mode of inhibition. Anticancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Unfortunately, all of the known K V 10.1 inhibitors also inhibit the highly similar cardiac hERG channel, and therefore these have limited potential for development into anticancer drugs that act through this novel mechanism of action. With the goal being to develop selective K V 10.1 inhibitors as potential anticancer drugs [53], we investigated their binding modes in the K V 10.1 channel pore using advanced molecular modeling methodologies. The creation of the common structure-based pharmacophore model for K V 10.1 inhibitors binding to the channel pore allowed us to compare it with the known hERG ligand-based pharmacophore models and to assess the potential for targeting the K V 10.1 channel pore for the development of K V 10.1-selective anticancer agents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, all of the known K V 10.1 inhibitors also inhibit the highly similar cardiac hERG channel, and therefore these have limited potential for development into anticancer drugs that act through this novel mechanism of action. With the goal being to develop selective K V 10.1 inhibitors as potential anticancer drugs [53], we investigated their binding modes in the K V 10.1 channel pore using advanced molecular modeling methodologies. The creation of the common structure-based pharmacophore model for K V 10.1 inhibitors binding to the channel pore allowed us to compare it with the known hERG ligand-based pharmacophore models and to assess the potential for targeting the K V 10.1 channel pore for the development of K V 10.1-selective anticancer agents.…”
Section: Resultsmentioning
confidence: 99%
“…Ligands that have been reported to inhibit K V 10.1, but where the mechanism of action is not through the block of the potassium ion flux by binding to the central cavity of the channel, should therefore not fit our pharmacophore model. Our model was tested on such a virtual library (Supporting Information Table S3) that was constructed from ligands collected in a review article [17], with the addition of our newly identified set of K V 10.1 inhibitors [53]. The pharmacophore model identified 16 of 61 active compounds.…”
Section: Creation Of the Merged Structure-based Pharmacophore Modelmentioning
confidence: 99%
“…Although the multi-target characteristics of natural products can decrease drug resistance, they complicate mechanistic studies. Currently, many new techniques for target prediction are available, such as reverse molecular docking and 3D pharmacophore modeling techniques 211 , 212 . Wei et al 213 have used the parameters of protein-ligand conformation interaction patterns as important indicators for target prediction and screening; this new strategy for target prediction effectively improved the accuracy of small molecule target identification.…”
Section: Discussionmentioning
confidence: 99%
“… 143 This approach has been particularly helpful for the identification of ligands, targeting membrane proteins. 146 , 147 …”
Section: Introductionmentioning
confidence: 99%
“… 143 Thus, the combinatory strategy including docking, virtual screening, de novo drug design, molecular simulations and the experimental validation by electrophysiological measures have allowed the development and a successful search for small modulators. 146 , 147 For the K + channels, a three-dimensional structure of representative K + subunits (Kv, K2P, and Kir) has been reported, providing insights into how these channels can be used to design specific modulators for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%